Organizacija mladinskega skrbstva v mestni občini Maribor v obdobju med obema vojnama - Dobaja, Dunja (Studia Historica Slovenica, 2021)
The article, based on archival material, presents the organization of youth care in the municipality of Maribor in the scope from the period between the two world wars. It puts the basic theme in a broader context and draws attention to the problems of the state and lower authorities in caring for minors. The broader context serves the author only as a framework for easier understanding of the basic topic, as she presented the care for children and mothers in detail in her monograph, in which she only touched upon youth care at the municipal level. The present article is thus a continuation of the author’s research into youth care in pre-war Slovenia, with its organization at the level of the city municipality, specifically Maribor, at the forefront.
Keywords: 1918-1941; childreen's shelter; childreen's station; city municipality; interwar period; Maribor; otroško skrbstvo; social history; socialna zgodovina; youth care; youth home